Knockdown of SLC38 Transporter Ortholog – CG13743 Reveals a Metabolic Relevance in Drosophila - Tanya Aggarwal (Frontiers in Physiology, 2020)
Solute Carrier (SLC) is a cluster of families of membrane bound transporters, of which many members lack defined substrate profile, and many more are poorly characterized. Many play a vital role in regulating metabolic systems, protein synthesis, and post translational modifications. SLC38 is one of the families of SLCs, which are also known as sodium-coupled neutral amino acid transporters (SNATs). In mice, it has 11 members (SNAT1-11) but in Drosophila there are two homologs for the SLC38 family; CG13743 and CG30394. Here, we show characteristics of Drosophila CG13743 which closely resembles SLC38A11 in humans. SLC38A11 still remains an orphan member of the SLC38 family which has not been functionally well studied. We used the UAS-GAL4 system to investigate and control gene expression using RNAi lines for ubiquitous knockdown of the CG13743 gene. It was found to be expressed mainly in salivary gland and brain. Knockdown flies had reduced body weight and consumed less sugar compared with controls. The gene knockdown also affected stored energy pools (lipids and glycogen) and influenced feeding pattern and total activity. In all, this shows novel findings for the characterization of CG13743 in Drosophila and a possible role in maintaining general metabolic pathways and behavior of the fly.